Blended Learning's Effect Toward Learning Achievement Post Covid 19 Pandemic - Norma Eralita; Frida Amriyati Azzizzah (Universitas Islam Indonesia, 2023)
Blended learning is one of the learning models used after the COVID-19 pandemic at Nahdlatul Ulama Al Ghazali University. Blended learning integrates technology that combines or mixes face-to-face and computer-based (online) learning. During the stages of the learning process, the lecturer prepares teaching materials in the form of PowerPoints or videos that can be accessed through learning media including EdLink, Zoom Meeting, Google Meet, and other electronic media. The purpose of this study was to determine the effect of blended learning on learning achievement. The research method used is a quantitative method because the research data is in the form of numbers and analysis using statistics. The analysis used is a linear regression analysis with a population of mechanical engineering students. The number of samples used amounted to 34 students. Data collection techniques in the form of tests and questionnaires with a Likert scale from the results of the normality and linearity tests, it shows a sig value of 0.200 and 0.177, which states that the data is normally distributed and linear. Based on the linear regression test, it was determined that the t count was 3.296 > ttable 2.037 with a regression coefficient value of 0.331. It can be concluded that there is an influence between the x variable (blended learning) and the y variable (learning achievement).